1992
DOI: 10.1038/eye.1992.95
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic ophthalmia: Visual results with modern immunosuppressive therapy

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0
4

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 13 publications
4
38
0
4
Order By: Relevance
“…This series also reveals that most patients with SO can have a good visual outcome, as was found in earlier reports [5,10,11,14]. We found that initiation of treatment soon Kilmartin et al [14] 1997-1998 56 Chan et al [5] 1982-1992 28 Jennings and Tessler [11] 1974-1985 25…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This series also reveals that most patients with SO can have a good visual outcome, as was found in earlier reports [5,10,11,14]. We found that initiation of treatment soon Kilmartin et al [14] 1997-1998 56 Chan et al [5] 1982-1992 28 Jennings and Tessler [11] 1974-1985 25…”
Section: Discussionsupporting
confidence: 78%
“…Firstly, all patients in our series are Asians, as is expected from Singapore's geographical location within Southeast Asia. Secondly, we report a much higher proportion of surgically induced SO than the other reports do [5,10,11,14]. Table 2 shows that the proportion of surgically induced SO has increased over the years, with a corresponding decline in SO after accidental, non-surgical trauma.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In der Literatur sind uneinheitliche Therapieschemata von 1 mg/kg Körpergewicht oraler Prednisolongabe bis zu initial 1000 mg intravenöser Verabreichung und langsamer Reduktion beschrieben [1,4,[6][7][8]. Eine langfristige Immunsuppression für insgesamt 6 bis 12 Monate wird empfohlen.…”
Section: Diskussionunclassified
“…Azathioprin ist ein Purinanalogon und das Prodrug von Mercaptopurin, das die DNA-und RNASynthese enzymatisch blockiert. Die erfolgreiche Anwendung von Azathioprin bei der sympathischen Ophthalmie wurde bereits mehrfach vorbeschrieben[6][7][8][9]. Unser Patient zeigte unter der sofortigen systemischen Hochdosiskortisontherapie und der Umstellung auf das Immunsuppressivum Azathioprin ein erfreulich schnelles Therapieansprechen und einen positiven Krankheitsverlauf.…”
unclassified